The Test of DLCO Is A Valuable Predictor for Prognostic Determination of Patients with Chronic Obstructive Pulmonary Disease - Dina Okfina Ria; Suradi Suradi; Jatu Aphridasari; Reviono Reviono; Dono Indarto (Jurnal Respirologi Indonesia, 2018)
Background: Chronic obstructive pulmonary disease (COPD) is characterized by permanent and progressive air way obstruction. In terms of morbidity, this disease is the first highest pulmonary disease in the world. DLCO is used for measurement of gas transfer from alveoli to blood capillary and Hb level is one of the main factors affecting the gas transfer. The aim of this study was to examine prognosis of patients with stable COPD using lung function, DLCO and Hb tets. Methods: Consecutive sampling was used to recruit 33 outward patients who suffered stable COPD and visited the Lung Clinic at Public Hospital dr. Moewardi Surakarta. Classification of COPD was determined using GOLD 2016. Airway and lung functions were examined using spirometry and single breath DLCO. Hb level was measured using cyamethemoglobin method. All collected data were analyzed using student t test and p value was set up P